Admission Levels of Interleukin 10 and Amyloid β 1–40 Improve the Outcome Prediction Performance of the Helsinki Computed Tomography Score in Traumatic Brain Injury - Posti, Jussi P.; Takala, Riikka S. K.; Raj, Rahul; Luoto, Teemu M.; Azurmendi, Leire; Lagerstedt, Linnéa; Mohammadian, Mehrbod; Hossain, Iftakher; Gill, Jessica; Frantzén, Janek; van Gils, Mark; Hutchinson, Peter J.; et al. (Frontiers in Neurology, 2020)
Background: Blood biomarkers may enhance outcome prediction performance of head computed tomography scores in traumatic brain injury (TBI). Objective: To investigate whether admission levels of eight different protein biomarkers can improve outcome prediction performance of the Helsinki Computed Tomography Score (HCTS) without clinical covariates in TBI. Materials and methods: Eighty-two patients with computed tomography positive TBIs were included in this study. Plasma levels of β-amyloid isoforms 1-40 (Aβ40) and 1-42 (Aβ42), glial fibrillary acidic protein, heart fatty acid binding protein, interleukin 10 (IL-10), neurofilament light (NF-L), S100B and total tau were measured within 24h from admission. The patients were divided into favorable [Glasgow Outcome Scale-Extended (GOSE) 5–8, n=49] and unfavorable (GOSE 1¬¬–4, n=33) groups. Outcome was assessed 6–12 months after injury. An optimal predictive panel was investigated with sensitivity set at 90–100%. Results: The HCTS alone yielded a sensitivity of 97.0% (95%CI:90.9–100) and specificity of 22.4% (95%CI:10.2–32.7), and partial area under the curve of receiver operating characteristic (pAUC) of 2.5% (95%CI:1.1–4.7), in discriminating patients with favorable and unfavorable outcome. The threshold to detect a patient with unfavorable outcome was a HCTS>1. The three best individually performing biomarkers in outcome prediction were Aβ40, Aβ42 and NF-L. The optimal panel included IL-10, Aβ40 and the HCTS reaching a pAUC of 3.4% (95%CI:1.7–6.2) with a sensitivity of 90.9% (95%CI:81.8–100) and specificity of 59.2% (95%CI:40.8–69.4). Conclusion: Admission plasma levels of IL-10 and Aβ40 significantly improve the prognostication ability of the HCTS following TBI.